Clustering golfers through force plate analysis - Shepherd, J.; Henrikson, E.; Lynn, S.; Wood, P. (Proceedings, 2020)
Golf is a sport which requires players to use ground interaction to generate clubhead speed in order to propel the ball towards the target. Force platforms are a technology which can be used to measure these ground reaction forces. Golfers generate force through a combination of jumping, sliding or twisting actions during the swing. Understanding how golfers generate these forces and if there are any groups which golfers could be clustered into could be used to enhance golf instruction as well as clubhead design or fitting practices for golf equipment. A total of 105 right-handed experienced golfers (handicap mean = 8.32 ± 8.31) consented to participate in the study of different swing speeds (31 below 95 mph, 41 over 105 mph and 33 between 95 and 105 mph). A calibrated single force plate was used for the test which sampled at 1000 Hz and recorded force and moment data in three axes. After a self-guided warm up, the players were instructed to hit five 7-iron shots and five drives to the best of their ability in an indoor hitting bay which used a launch monitor to record the club delivery and ball flight information. It was found that handicap or swing speed did not dictate the primary force production mechanism (sliding, jumping or twisting/spinning). This knowledge could aid engineers to design equipment better suited to the individual and help coaches build individualized programs to create power and clubhead speed in all players.